Proses Fonologi Bahasa Belanda - Sri Sulihingtyas (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2013)
Phonological process is a process of change in the sounds of language that occurs when a person speaks. This process occurs due to the adjustment of speech organs to sounds that will be generated by the speech organs. This process may occur directly and we do not realize, because this process happens automatically by every speech organs we have said. Even if we try to realize the phonological processes that occur, we may actually be difficult to produce these sounds. This paper deals with some phonological processes in Dutch language. The Dutch language has also some phonological processes that allow for some adjustments to the instrument of articulation he said so that it can produce the desired sounds of language.